Determinants of earnings quality: The role of managerial ownership - Cahya Wahyuningtyas; Taufikur Rahman (Akuntansi dan Teknologi Informasi, 2023)
This research analyzes and determines the effect of investment opportunity set, earnings persistence, and capital structure on earnings quality by making managerial ownership a moderating variable. This research is classified as a type of quantitative research with panel data obtained from secondary financial report data that has been published through Indonesian Stock Exchange website. Furthermore, the research sample was filtered using purposive sampling technique with several predetermined criteria to obtain 30 manufacturing companies registered at ISSI for 2019-2021 that met the criteria with a 3-year observation span. So, the total sample used was 90. Data analysis in this study used Moderated Regression Analysis. After testing with the Eviews 9 tools, the results show that the IOS variable has a positive and significant effect on earnings quality, earnings persistence has a negative but significant effect, while earnings persistence has no effect on earnings quality. Managerial ownership can only moderate the IOS’ relationship to earnings quality, however earnings persistence and capital structure variables cannot be moderated by managerial ownership in influencing earnings quality